A Pharmaceutico-Analytical Study of Different Samples of Shilajit (AYUSHDHARA, 2025)
Shilajit (Asphaltum punjabianum) is an important and widely used drug in Ayurveda. Shodhana of Shilajit was widely mentioned but the methods of analysis were restricted. The composition of Shilajit mainly depends on the variety of plants that are associated with the rocks. Even though the precise origin of Shilajit is unknown, its popularity is increasing in today's society. Despite being commonly used, there is a lack of data regarding the analytical profile of Shilajit. Aim: An effort has been made to purify both natural and market samples as per AFI and analyze both raw and Shudha Shilajit samples, study their composition, and create the data to help generate the standard parameters of the Shudha Shilajit which will help to reduce the research gap of Shilajit analysis.